2023
DOI: 10.35484/ahss.2023(4-i)17
|View full text |Cite
|
Sign up to set email alerts
|

Spillover of Workplace Incivility on Family Satisfaction of Nurses: Role of Work-to-Family Conflict and Family Support

Abstract: This study aims to examine the association between workplace incivility and family satisfaction through the mediating variable of work-family conflict. Family support is used as the moderating variable in the association between workplace incivility and work-family conflict. Data were collected from 420 staff nurses working in the public sector hospitals of Punjab, Pakistan. PLS-SEM was used to test the proposed relationships. Employees who have experienced workplace incivility reported lower levels of family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Furthermore, as observed by Andersson and Pearson Tit-for-Tat paradigm of workplace incivility, isolated instances of uncivil behaviour or attitude can result to employees' satisfaction (Raza et al, 2023;Razzaq et al, 2023). Thus, there are ample reasons to infer that incivility is connected with numerous negative occupational, psychological, physical health, and organizational outcomes (Raza et al, 2023;Razzaq et al, 2023;Xiao et al, 2023). Regardless of the viewpoints shared in the existing literature on the impact of workplace incivility on performance, mental wellness and other organizational outcomes, it is important to note that there is a lack of empirical evidence to definitively confirm or refute the influence of workplace incivility on employee satisfaction, particularly within the context of small and medium scale enterprises (SMEs) in Nigeria, hence a research gap exists in this specific area.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Furthermore, as observed by Andersson and Pearson Tit-for-Tat paradigm of workplace incivility, isolated instances of uncivil behaviour or attitude can result to employees' satisfaction (Raza et al, 2023;Razzaq et al, 2023). Thus, there are ample reasons to infer that incivility is connected with numerous negative occupational, psychological, physical health, and organizational outcomes (Raza et al, 2023;Razzaq et al, 2023;Xiao et al, 2023). Regardless of the viewpoints shared in the existing literature on the impact of workplace incivility on performance, mental wellness and other organizational outcomes, it is important to note that there is a lack of empirical evidence to definitively confirm or refute the influence of workplace incivility on employee satisfaction, particularly within the context of small and medium scale enterprises (SMEs) in Nigeria, hence a research gap exists in this specific area.…”
Section: Discussionmentioning
confidence: 93%
“…More importantly, it has been found that incivility in the workplace has negative influence on people who witness uncivil behaviour directly (Raza et al, 2023;Razzaq et al, 2023). Furthermore, as observed by Andersson and Pearson Tit-for-Tat paradigm of workplace incivility, isolated instances of uncivil behaviour or attitude can result to employees' satisfaction (Raza et al, 2023;Razzaq et al, 2023). Thus, there are ample reasons to infer that incivility is connected with numerous negative occupational, psychological, physical health, and organizational outcomes (Raza et al, 2023;Razzaq et al, 2023;Xiao et al, 2023).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations